2022
DOI: 10.1002/adem.202200620
|View full text |Cite
|
Sign up to set email alerts
|

Achieving Superplastic Elongations in an AZ80 Magnesium Alloy Processed by High‐Pressure Torsion

Abstract: Processing magnesium alloy by High-Pressure Torsion (HPT) is a technique used successfully to refine the grains of an alloy to the submicrometer and nanometer scale to produce an ultrafine grained microstructure. Grain refinement can improve the mechanical properties of magnesium alloys as well as enhancing its ductility and providing a potential for exhibiting superplastic behaviour at elevated temperature. Research was conducted to process the AZ80 magnesium alloy by HPT at room temperature for different num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Unlike other SPD methods, which have been reported to induce microcracking in Mg, HPT has been shown to induce grain refinement with greater fractions of volumes with high angles of misorientation without microcracking even when processed at low temperatures (Alsubaie et al, 2022;Figueiredo & Langdon, 2019). This is attributed to the application of the hydrostatic pressure in the HPT process (Alsubaie et al, 2022;Figueiredo & Langdon, 2019). Harai et al (2008) investigated the mechanical properties of AZ61 Mg alloy processed with High-Pressure Torsion (HPT) at the temperature of 423 K. Their tensile test results showed that the maximum of 620% superplastic elongation could be achieved at the temperature of 473 K. This was slightly bettered by (Alsubaie et al, 2022) who achieved a superplastic elongation of 645% in AZ80 at a temperature 573 K. Harai et al (2008) further conducted the microstructural examination that showed an excellent grain refinement on AZ61 magnesium alloy samples with the average sizes of 0.22 µm and 0.11 µm.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…Unlike other SPD methods, which have been reported to induce microcracking in Mg, HPT has been shown to induce grain refinement with greater fractions of volumes with high angles of misorientation without microcracking even when processed at low temperatures (Alsubaie et al, 2022;Figueiredo & Langdon, 2019). This is attributed to the application of the hydrostatic pressure in the HPT process (Alsubaie et al, 2022;Figueiredo & Langdon, 2019). Harai et al (2008) investigated the mechanical properties of AZ61 Mg alloy processed with High-Pressure Torsion (HPT) at the temperature of 423 K. Their tensile test results showed that the maximum of 620% superplastic elongation could be achieved at the temperature of 473 K. This was slightly bettered by (Alsubaie et al, 2022) who achieved a superplastic elongation of 645% in AZ80 at a temperature 573 K. Harai et al (2008) further conducted the microstructural examination that showed an excellent grain refinement on AZ61 magnesium alloy samples with the average sizes of 0.22 µm and 0.11 µm.…”
Section: Introductionmentioning
confidence: 92%
“…SPD methods have been widely investigated and acclaimed to attain material formability and grain refinement as well as overcoming a number of other well-known problems such as residual porosity and sample impurities (Valiev et al, 2000;Zhilyaev & Langdon, 2008;Zhu et al, 2004). Unlike other SPD methods, which have been reported to induce microcracking in Mg, HPT has been shown to induce grain refinement with greater fractions of volumes with high angles of misorientation without microcracking even when processed at low temperatures (Alsubaie et al, 2022;Figueiredo & Langdon, 2019). This is attributed to the application of the hydrostatic pressure in the HPT process (Alsubaie et al, 2022;Figueiredo & Langdon, 2019).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…where έ is strain rate, T is absolute temperature and d is the diameter of grains (grain size). Many severe plastic deformation (SPD) methods have been studied upon for the grain refinement and superplastic behaviour of the Mg alloys like high pressure torsion (HPT) [15], accumulative roll bonding (ARB) [16], equal channel angular processing (ECAP) [17], multi-axial forging (MAF) [18] and friction stir processing (FSP) [19]. FSP, principally evolved from solid-state friction stir welding (FSW) process, is garnering more attention in comparison to other SPD practices owing to the beneficial features of lower cycle periods, larger microstructural refinement in single pass, less complicated working set-up and procedural steps [20].…”
Section: Introductionmentioning
confidence: 99%